(untitled) (American Journal of Arts and Human Science, 2025)
The exploration of code-mixing and code-switching phenomena, especially in online contexts, has predominantly focused on English/Chinese bilinguals, leaving a gap in understanding these linguistic phenomena among other bilingual groups engaging in online discourse. This study aims to bridge this gap by investigating the motivations underlying code-mixing and code-switching among Yoruba/English bilinguals within selected Facebook forums. Data were meticulously collected from two distinct Facebook forums: ‘Ondo State people’ and ‘Nigerian Online Community’, serving as a window into the digital linguistic practices of the Yoruba/English bilingual community. Employing Halliday’s functional theory of language as the analytical lens, this study uncovered three core motivations driving code-mixing and code-switching: linguistic, social, and computer-related motivations. Linguistically, the motivating factors identified include lexical gaps, euphemism/dysphemism, and a lower level of English competence. Social motivations were tethered to language identity and language attitudes, while computer-related motivations were encapsulated by computer-aided code-switching and online linguistic creativity. This analysis underscores the unique ‘linguistic world’ of Facebook forums, where traditional language usage is streamlined, adapted, and evolved, reflecting a dynamic interplay of linguistic, social, and digital factors in modern bilingual communication.